2008
DOI: 10.1073/pnas.0707522105
|View full text |Cite
|
Sign up to set email alerts
|

Extreme polyploidy in a large bacterium

Abstract: Cells rely on diffusion to move metabolites and biomolecules. Diffusion is highly efficient but only over short distances. Although eukaryotic cells have broken free of diffusion-dictated constraints on cell size, most bacteria and archaea are forced to remain small. Exceptions to this rule are found among the bacterial symbionts of surgeonfish; Epulopiscium spp. are cigar-shaped cells that reach lengths in excess of 600 m. A large Epulopiscium contains thousands of times more DNA than a bacterium such as Esch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
146
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(160 citation statements)
references
References 65 publications
5
146
1
3
Order By: Relevance
“…Indeed, recent studies suggest that the bacterial signal recognition particle may slow or arrest the translation of membrane proteins (24,25), which could provide time not only for the ribosome-nascent chain complex to engage the secretion machinery but also for transcription to terminate before membrane insertion commences. To our knowledge, transertion has never been demonstrated, although observations of plasmid supercoiling (26), nucleoid collapse from translation inhibitors (10), and DNA localization in large cells (27) can be explained by such a mechanism. The direct observation of locus repositioning to the membrane reported here is consistent with a transertion mechanism as well.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies suggest that the bacterial signal recognition particle may slow or arrest the translation of membrane proteins (24,25), which could provide time not only for the ribosome-nascent chain complex to engage the secretion machinery but also for transcription to terminate before membrane insertion commences. To our knowledge, transertion has never been demonstrated, although observations of plasmid supercoiling (26), nucleoid collapse from translation inhibitors (10), and DNA localization in large cells (27) can be explained by such a mechanism. The direct observation of locus repositioning to the membrane reported here is consistent with a transertion mechanism as well.…”
Section: Discussionmentioning
confidence: 99%
“…Such extreme levels of polyploidy are rare in prokaryotes with a single, disputed, description of polyploidy in the large bacterium Epulopiscium (Bresler et al, 1998;Robinow and Angert, 1998). PCR quantification of the Epulopiscium species type B genome suggested that this bacterium is highly polyploid with an individual cell containing 410 000 copies of its genome (Bresler and Fishelson, 2003;Mendell et al, 2008;Liu, 2009). If cyanobacterial akinetes represent starvation or aging responses, similar to those that induce stationary phase, we would expect akinetes to show a decrease in polyploidy, such as that reported for H. volcanii (Breuert et al, 2006).…”
Section: Genome and Ribosome Multiplication In Akinetes A Sukenik Et Almentioning
confidence: 99%
“…Although polyploidy is well appreciated in plants , many different animal tissues, including the skin, gut, placenta, liver, brain and blood have polyploid cells (Table 1) (Laird et al, 1980;Corash et al, 1989;Fox et al, 2010; Hedgecock and White, 1985;Melaragno et al, 1993;Sherman, 1972;Unhavaithaya and Orr-Weaver, 2012;Zanet et al, 2010). Interestingly, endoreplication is not limited to multi-cellular organisms, with examples described in ciliated protozoa (Yin et al, 2010) and even bacteria (Mendell et al, 2008).Two primary forms of endoreplication have been described: endocycling and endomitosis (Fig. 1).…”
mentioning
confidence: 99%